Enterprise applications, markets and services in the finance industry : 9th International Workshop, FinanceCom 2018, Manchester, UK, June 22, 2018, Revised Papers /: 9th International Workshop, FinanceCom 2018, Manchester, UK, June 22, 2018, Revised Papers. (2019) - Unknown
No abstract available